Pembelajaran Direct Instruction dengan Media Lagu Terhadap Prestasi Belajar Matematika di SD Se-Kecamatan Laweyan - Januar Budi Asmari (LPPM Press, 2013)
This research has purpose to determine which one providing better learning achievement between direct instruction learning with song and direct instructionlearning without song. In this research, students’ learning achievementis limited to the fourth grade teaching material of elementary schoolin circumference and area of parallelogram. The result of this research produces songsare consisting of circumference, area of parallelogram, and triangle teaching materials. This research is conducted to all elementary schools in Laweyan. Two schools are randomly taken as the samples, and then one class is taken from each school, therefore thereare two classes. The first sample as the experiment class (direct instruction learning with song) and the second sample as the control class (direct instruction learning without song). The research is quasi-eksperimental research. The research methods used are test and documentation method. The research data analysis is using t-test. Based on the resultof the research is obtained t = -2,198 DK, then H0 is subtracted. Therefore it can be conclude that there are differences mathematic learning achievement between direct instruction learning with song and direct instruction learning without song. If it is observed on the average, learning achievement of direct instruction learning with song is better than direct instruction learning without song